2015
DOI: 10.4049/jimmunol.1402454
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Splicing in the Proteasome Creates a Novel Type of Antigen with an Isopeptide Linkage

Abstract: The proteasome is able to create spliced Ags, in which two distant parts of a protein are excised and ligated together to form a novel peptide, for presentation by MHC class I molecules. These noncontiguous epitopes are generated via a transpeptidation reaction catalyzed by the proteasomal active sites. Transpeptidation reactions in the proteasome follow explicit rules and occur particularly efficiently when the C-terminal ligation partner contains a lysine or arginine residue at the site of ligation. Lysine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
(62 reference statements)
1
24
0
Order By: Relevance
“…The data led to the hypothesis that the catalytically active threonine residues in the standard proteasome form O ‐acyl intermediates with the N‐terminal peptide fragment which is then subject to nucleophilic attack by the N‐terminus of another peptide fragment, which forms the C‐terminal end of the spliced peptide (Figure ). This mechanism has since been supported by several other studies . In addition, Ebstein et al .…”
Section: Mechanisms and Motifssupporting
confidence: 68%
See 1 more Smart Citation
“…The data led to the hypothesis that the catalytically active threonine residues in the standard proteasome form O ‐acyl intermediates with the N‐terminal peptide fragment which is then subject to nucleophilic attack by the N‐terminus of another peptide fragment, which forms the C‐terminal end of the spliced peptide (Figure ). This mechanism has since been supported by several other studies . In addition, Ebstein et al .…”
Section: Mechanisms and Motifssupporting
confidence: 68%
“…Peptide splicing can introduce an isopeptide bond between the two protein fragments . The peptide bonds between adjacent amino acids in proteins and peptides form between the α amino group of the C‐terminal amino acid and the carboxylic acid of the N‐terminal amino acid.…”
Section: Spliced Class I Epitopesmentioning
confidence: 99%
“…In addition, we show that splicing-prone sequences are ligated with high efficiency, that many spliced products may be formed from a single protein, and that splicing of long peptides predominantly occurs via cis-splicing, all suggesting that protein splicing may play a much more significant role in immunity than previously assumed. In an accompanying article, we show that the proteasome can form a novel type of Ag containing an isopeptide linkage, further extending the spliced Ag repertoire (35). Ag splicing would ensure that a more diverse peptide repertoire reaches the cell surface, which increases the chance of recognition by CD8 + T cells and ultimately of elimination of the malignant or infected cell by the immune system (3,(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Studying in vitro peptide digests, Berkers et al (38) showed that the ⑀-amino group of lysine residues could also perform a nucleophilic attack on the acyl-enzyme intermediate, leading to the formation of a new type of spliced peptide containing an isopeptide bond (hereafter called spliced isopeptide). Surprisingly, their results show that splicing by ⑀-amines was only 10-fold less efficient than splicing by ␣-amines.…”
Section: Peptide Splicing By Isopeptide Linkagementioning
confidence: 99%
“…Strikingly, the presence of an isopeptide bond was shown to protect the spliced isopeptide from proteasome degradation. This increased stability of spliced isopeptides might have actually facilitated their identification in the first place but somewhat biased the evaluation of the splicing efficiency by ⑀-amines compared with ␣-amines; in their experiments, Berkers et al (38) performed proteasome digestions over 16 -24-h periods, which might have favored the secondary degradation of spliced peptides over spliced isopeptides, thereby artificially increasing the production rate of these spliced isopeptides compared with the canonical spliced peptides. Moreover, although spliced isopeptides were shown to activate patient-derived CD8 ϩ T cells in vitro, the presence of spliced isopeptides at the cell surface has not yet been demonstrated, questioning whether this phenomenon really occurs in physiological conditions.…”
Section: Peptide Splicing By Isopeptide Linkagementioning
confidence: 99%